Politik Luar Negeri Tiongkok Sejak Tahun 1978: Transisi, Rebalancing dan Aktivisme - Muhammad Erza Pradana (Department of International Relations, Hasanuddin University, 2022)
This article seeks to explain and analyze the changes and continuity in China’s foreign policy since 1978. The rise of China is perceived as both remarkable and threatening by many countries. Like all great powers, China’s rising power has been to further assert its dominance especially in Asia. However, since its declaration in 1949, China’s foreign policy had undergone significant adjustments to adapt with both domestic and international situation. In this article, the author the author divides the development of post-Mao Chinese foreign policy into 3 main phases, namely, Transition, Rebalancing and Activism. Of the three phases, the author will explain and analyze the changes and continuity that occur in the development of China's foreign policy. This artcile uses the Neoclassical Realist Theory of foreign policy to explain the evolution in China’s foreign policy. The author uses a qualitative approach with the literature study method as a data collection technique. Artikel ini berusaha menjelaskan dan menganalisis perubahan dan kesinambungan kebijakan luar negeri China sejak 1978. Kebangkitan China dianggap luar biasa dan mengancam oleh banyak negara. Seperti semua kekuatan besar, kekuatan China yang meningkat telah semakin menegaskan dominasinya terutama di Asia. Namun, sejak dideklarasikan pada tahun 1949, kebijakan luar negeri China telah mengalami penyesuaian yang signifikan untuk beradaptasi dengan situasi domestik dan internasional. Dalam artikel ini, penulis membagi perkembangan politik luar negeri China pasca era Mao menjadi 3 fase utama, yaitu Transisi, Rebalancing dan Aktivisme. Dari ketiga fase tersebut, penulis akan menjelaskan dan menganalisis perubahan dan kontinuitas yang terjadi dalam perkembangan politik luar negeri China. Artikel ini menggunakan Teori Neoklasik Realis kebijakan luar negeri untuk menjelaskan evolusi dalam kebijakan luar negeri China. Penulis menggunakan pendekatan kualitatif dengan metode studi kepustakaan sebagai teknik pengumpulan data.